(untitled) (London Journal of Medical and Health Research, 2026)
The use of medications in conventional dosages guarantees their mechanism of action and provides the expected biological effects. Clinical trials and research on substances approved by the national health agency justify their clinical efficacy and demonstrate the risk-benefit of the medication, but they also contain some information on the toxic effects on the body when used in doses above the recommended. A bibliographic review was conducted targeting some classes of medications, such as antipsychotics, SSRI antidepressants (serotonin reuptake inhibitors), tricyclic and tetracyclic antidepressants, lithium, benzodiazepines, nonsteroidal anti-inflammatory drugs (NSAIDs), anticholinergics, digitalis, opiates, opioids and thyroid hormone, to update knowledge on drug poisoning protocols established by other institutions that are references in the subject, making it possible to identify symptoms and define treatments for these cases. Thus, in drug poisoning, irreversible effects can be observed in the short and long term, and even death if not treated appropriately. The available protocols used in reference centers and units for this type of care describe the identification of possible associated toxic syndromes, symptom management, symptomatic treatment and the antidote that can be used. Therefore, clinical research and pharmacovigilance contribute to the elucidation and understanding of toxicological effects, being an updated source based on the availability of information that occurs in hospital practice.